The Increased Circulating Plasma Levels of Vascular Endothelial Growth Factor in Patients with Type 1 Diabetes Do Not Correlate to Metabolic Control - Kailash Singh; Stellan Sandler; Daniel Espes (Journal of Diabetes Research)
Aim. To characterize the plasma levels of vascular endothelial growth factor (VEGF) in type 1 diabetes mellitus (T1D) and its relation to both present and historical metabolic control and microvascular complications. Methods. Plasma levels of VEGF and routine clinical parameters were analyzed in 115 patients with long-standing T1D and 45 healthy controls (HC). All patients were under clinical routine diabetes treatment at Uppsala University Hospital. Results. The plasma levels of VEGF were increased by 37% in patients with T1D when compared to HC (18.2±0.8 versus 13.2±1.0 pg/ml, p<0.001). The levels of VEGF correlated to insulin needs and BMI but not to present or historical metabolic control. The levels of VEGF were similar in patients with T1D and microvascular complications (microalbuminuria and retinopathy) when compared with patients without microvascular complications. Historical HbA1c levels were found to be the best predictor for present metabolic control. Conclusion. Circulating plasma levels of VEGF do not correlate to present or historical metabolic control in long-standing T1D and the levels are not affected by the presence of microvascular complications.